Hybrid Sindbis/Epstein-Barr virus episomal expression vector for inducible production of proteins - Lidia Ivanova; Johanna Brändli; Philippe Saudan; Martin F. Bachmann (BioTechniques)
Alphavirus vectors are attractive as recombinant protein expression systems due to the high level of gene expression achieved. The combination of two mutations in the viral replicase, which render the replicase noncytopathic and temperature-sensitive, allowed the generation of a DNA-based vector (CytTs) that shows temperature inducible expression. This vector is of significant value for the production of toxic protein. However, like for other stable expression systems, tedious screening of individual cell clones are required in order to get a high producer cell clone. To circumvent this, we generated an episomally replicating vector by introducing an Epstein-Barr virus mini-replicon unit into CytTs. This novel vector allowed rapid generation of cell populations that showed tight regulation of expression and comparable expression levels to the ones achieved with high producer cell clones with CytTs. Moreover, protein production with selected cell populations could easily be scaled-up to a fermentation process.